SCHOOL MANAGEMENT STRATEGY IN ENSURING EARLY CHILDHOOD SAFETY IN RA SHAZIA PALEMBANG - Febrianti, Viana; Wahyuni, Gusti (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2025)
This study aims to describe school management strategies in ensuring early childhood safety in the Raudhatul Athfal (RA) environment. The background of this research is based on the increasing cases of violence, accidents, and neglect against children in PAUD units, as well as the importance of the role of school management in building an effective and sustainable protection system. This study uses a descriptive qualitative approach with a case study method carried out at RA Shazia Palembang. Data collection techniques are carried out through in-depth interviews, observations, and documentation. The research subjects include school principals, teachers, and support staff. The results of the study show that although schools already have policies in the form of safety SOPs, implementation in the field has not been optimal. Teachers have not received special training, evacuation simulations have never been carried out, and incident reporting systems have not been actively functioning. Most of the physical facilities of the school have met the standards, but unsafe facilities are still found. Security evaluation and monitoring are still incidental and not yet system-based. This research contributes to the development of early childhood safety management and recommends the need for periodic training, facility audits, and parental involvement in risk prevention efforts.